OPrlMALISASI EKSPOR KAYU LAPIS INDONESIA: (Studi Kasus Pabrik Kayu Lapis di Propinsi Sumatra Selatan) - Satria Astana; Hariyatno Dwiprabowo; Kirsfianti Linda (Jurnal Penelitian Hasil Hutan, 1991)
•Of the forat  pfoductt in •rndonei~,. plywood haa an •im~rlant  '1olitio1'•in mee~•the  need for•t~   f~reiln, ~• By the end of 1986. the contribution of plywood to the tQ.tal export value of forat  pro~ucta ~the     brggest.It accounted for 61. 40~  In the (Qllowingyea.r., the a.,erage gr:owthper. ye~r.of  the•pbwood  expor.t volume was 54.98_%. .          .                                                                                   : The a.im •of  thia atudy   ~  to •know   how far   the a~tual value• of. the plywood  export  aB the fore'!n exchange •Im reached the optimum.  To achieve the aim, two modelB (Model• I and Model II) of linier 11rograming were conatrueted. In •    thia caae, the study   waa conducted on the plywood  mill• in South Sumatra Province.                •                                                                                                                    •The rault   of  the study  revealB that the actual ualue of the plywood  export of thia region has not been optimum. The actual value of the export per month  waa USI 3 342 778 or USI 286. 1/m3. Meanwhile the export ~ue    per month based on the optimizing model of Model I and Model II iB  UBI 4 297 269 or US$'824.  9/m3 and UBI 4 537 673 or UBI 343. 2/m3  respectively.                                                                                                         To reach the optimum  value of export the market area and the export volume• need to be reallocated;tJn increasein volume export  by 1.35%  (Model I) or by  1.04'*'  (Model II) can cause a significant incre•e  in the export value comj'JtJl"ed with the ualue• gained by  the mill.Since the demand of  the Indonesian plywood  export iB prone to increaae, the reault of the optimizing modeZ. can be implemented. However, the optimizing reault of Model II iB preferred particularly with regard to the efficiency of f!&e forest re1ourceuse.